Three-tesla MRI biphasic angiography: a method for preoperative assessment of the vascular supply in renal tumours: a surgical perspective - Hora, Milan; Stránský, Petr; Trávníček, Ivan; Urge, Tomáš; Eret, Viktor; Kreuzberg, Boris; Baxa, Jan; Mírka, Hynek; Petersson, Fredrik; Hes, Ondřej; Ferda, Jiří (World journal of urology, 2013)
PURPOSE: The new generation of 3TMRI has improved spatial and time resolutions, which are favourable in imaging of the renal vasculature. In this study, we have compared the imaging findings of the renal blood vessels using 3TMRI and CT with intraoperative assessment of the renal vasculature as gold standard. METHODS: This prospective study was approved by the local ethical committee. Between 4/2011 and 12/2011, 80 patients with renal tumours underwent 3TMRA (angiography) (Magnetom SKYRA 3T, Siemens). Twenty of the patients were also examined with CT AG. The results of the CTA- and MRA-imaging studies were correlated with the intraoperative assessment of the renal vessels. RESULTS: Seventy patients (87.5 %) had a detailed intraoperative assessment of the renal vessels. The sensitivities for CTA and MRA were 88.2 and 88.6 %, respectively. All discrepancies between imaging studies and intraoperative findings were due to inability to identify small polar vessels. The results of MRA were concordant with CTA in 85.0 % of cases. The (three) discrepancies between MRI and CT were due to failure of MRI in identifying small polar vessels. CONCLUSIONS: (1) 3TMRA gives detailed information about the renal vasculature including its topographical anatomy. (2) With MRI, small aberrant vessels are more frequently missed than with CTA. (3) CTA remains the gold standard. However, MRA may be used for planning of laparoscopic operations. (4) The quality of the 3D reconstruction is highly depending on the skills of the radiologist.
Keywords: nádory ledvin; Imaging, Three-Dimensional; počítačová rentgenová tomografie; Sensitivity and Specificity; senzitivita a specificita; Humans; laparoskopie; ledviny; Kidney; lidé; magnetická rezonanční angiografie; Retrospective Studies; Tomography, X-Ray Computed; předoperační péče; Laparoscopy; zobrazování trojrozměrné; retrospektivní studie; Magnetic Resonance Angiography; Nephrectomy; Preoperative Care; nefrektomie; prospektivní studie; Kidney Neoplasms; Prospective Studies